Numerical investigation into the stability of earth dam slopes considering the effects of cavities. Issue 4 (10th January 2020) - Alateya, Hawraa; Ahangar Asr, Alireza
Abstract : Purpose: This study is an attempt to estimate the influence of the presence of cavities on the stability of slopes in earth dams under rapid drawdown conditions. The purpose of this paper is to study the influence of different factors, such as the diameter and location of cavities, in addition to their existence effects. Design/methodology/approach: A series of finite element simulation models were developed using PLAXIS 2D finite element software to analyse the stability of slopes in earth dams while considering various effects from cavities in the subsoil under rapid drawdown conditions. Findings: The results indicated that the presence of cavities and an increase in the diameter of cavities decreased the stability of the upstream face dramatically for all examined locations in a horizontal direction; however, this effect was less on the downstream side. The results also showed that variations in the location of cavities in the horizontal direction have a greater effect on the stability than those in the vertical direction. The results revealed that increasing shear strength parameters of embankment does not reduce the influence of cavities on stability when those cavities are in critical locations. Originality/value: A numerical model has been developed to simulate the effects of cavities on the stability of slopes in water-retaining structures/earth dams. The stability of earth dam slopes on upstream and downstream sides under rapid drawdown conditions considering various cavity effects, including their existence, diameter and location, were numerically analysed.